Influence of Gender on the Patient's Assessment of Restorations on the Upper Anterior Teeth - Ela KRISTEK ZORIĆ; Maja Žagar; Dubravka KNEZOVIĆ ZLATARIĆ (University of Zagreb. School of Dental Medicine, 2014)
Objective: The aim of this study was to assess the level of patients' satisfaction with appearance of maxillary anterior teeth restorations and to determine if there is a significant difference in patients' assessment of restoration appearance with regard to gender. Materials and methods: Two hundred subjects evaluated the colour, anatomical shape and surface texture of maxillary anterior teeth restorations (composite fillings, acrylic faceted metal crowns, porcelain-fused-to-metal crowns and all-ceramic crowns) in comparison with adjacent natural teeth. The data were expressed in patients' average assessment scores for colour, anatomical shape and surface texture as well as overall patients' average assessment scores for every type of restoration and overall patients' average assessment scores for colour, anatomical shape and surface texture of all the restorations in general. Patients also assessed the general impression of their maxillary anterior teeth restorations and rated it as satisfactory or unsatisfactory. Results: There was a statistically significant gender difference in patient assessment of colour and surface texture for composite fillings and the overall patient average assessment score for colour of all assessments (p <0.05). Women were more dissatisfied with the general impression of their restorations on the upper teeth than men (p >0.05). Only overall patients' average assessment score for composite restorations almost reached the level of significance (p = 0.069) on patients' general impression. Conclusion: Colour of the restorations and the composite material are significant factors which affect dental appearance of maxillary anterior teeth in patients.